Evaluation of the physical activity in children with functional gastrointestinal disorders - Belousova , Olga; Kazarian , Larysa (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Functional gastrointestinal disorders have been known for centuries. However, this concept appeared quite recently, and is currently a common pediatric problem. Interest in functional pathology is fully justified and understandable: despite the fact that functional diseases of the gastrointestinal tract do not pose a direct threat to the patient’s life, they significantly reduce the quality of his life. The problem of functional disorders is also complicated by the fact that they affect all strata of society, regardless of age, socio-economic status, gender or race. The active process of studying the clinical and anamnestic features of various nosological forms, predictors of functional disorders, combined functional disorders and prevention approaches is also due to significant economic damage due to direct and indirect costs of their treatment. The prevalence of functional gastrointestinal disorders in the world reaches 40.3 %, and among children's gastro pathology they occupy one of the leading places. More than half of children of various age groups have at least one of the symptoms, which is a cause of concern for both the child and the parents, as well as entails a violation of the microclimate in the family. The peak prevalence of various symptoms of disorders of the gastrointestinal tract occurs at school age and adolescents, who almost fill the appointment of a pediatrician and a pediatric gastroenterologist. If we trace the evolution of ideas about functional disorders of the digestive organs, it can be noted that it changed many times and influenced the understanding of the pathogenesis and, especially, the etiology of this nasology. According to the Rome Consensus IV (2016), functional gastrointestinal disorders are defined as disorders of the interaction of the «gut-brain» axis, taking into account this concept, a lot of time has been devoted to studying the role of various factors: genetic predisposition, infection theory, nature of feeding at an early age, hormonal imbalance, psychological state, food preferences, lifestyle and physical activity. An important aspect of studying predictors of functional bowel disorders is the level of physical activity of children and adolescents. In the process of studying literary data, it was noted that the role of insufficient physical activity in the development of functional gastrointestinal disorders remains not fully determined. Most of the materials are related to the adult population and critically few among children. That complicates the study of forecasting and prevention of a more severe course of functional dyspepsia and irritable bowel syndrome, and, as a consequence, to optimize therapy. The aim of the study was to assess the level of physical activity in children with FGID. Materials and methods. 72 children aged 8–14 with FGIR were observed. I group of study included 26 patients with combined functional dyspepsia (FD) and irritable bowel syndrome (IBS), the II group – 46 patients with FD. The control group included 22 healthy children. The diagnosis of FD and IBS were established based on the analysis of clinical symptoms according to the Rome IV criteria (2016). The PAQ-C questionnaire, developed by K. Kowalski, P. Kroker, and R. Donen, was used to assess PA in children. Research results. The total PA index in children with combined FD and SPC was 1,87 ± 0,07 and was lower compared to the group of children with FD (2,21 ± 0,05; p < 0,05) and the control group (2,75 ± 0,05; p < 0,01). The total PA index in children with FD is lower than in the control group (p < 0,01). Conclusion. Insufficient physical activity can be considered a risk factor for the development of functional gastrointestinal disorders in children.